Risk Factors of Recurrent Ectopic Pregnancy in Patients Treated With in vitro Fertilization Cycles: A Matched Case-Control Study - Tan, Yu; Bu, Zhi-qin; Shi, Hao; Song, Hui; Zhang, Yi-le (Frontiers in Endocrinology, 2020)
Objective: To study the risk factors for recurrent ectopic pregnancy (REP) in patients undergoing in vitro fertilization (IVF). Methods: This was a 1:4 matched case-control study that enrolled 227 REP patients and 908 matched intrauterine pregnancy (IUP) patients from the assisted reproductive technology (ART) center of the First Affiliated Hospital of Zhengzhou University from January 2012 to November 2019. Univariate analysis was carried out between the two groups for the occurrence of REP. Multivariate logistic regression analysis was used to explore the risk factors of REP after IVF. Results: The results of univariate analysis showed that there were significant differences in previous treatment of EP, stage of embryo and the number of embryos transferred between the two groups (all P <0.05). The other factors did not have a significant effect on the probability of developing REP. Multivariate logistic regression analysis showed that after adjusting for confounders, previous treatment of EP, type of embryos transferred and stage of embryo were related to the occurrence of REP (all P <0.05). Conclusion: Conservative treatment, frozen-thawed embryo transfer and cleavage embryo transfer were independent risk factors for REP after ART treatment.